The Influence of Raw Materials on Quality of Cattle Farm Waste Liquid Organic Fertilizer in Tuban Regency - Nia Nurfitria; Kuntum Febriyantiningrum (Justek : Jurnal Sains dan Teknologi, 2026)
Urine is a liquid waste of cattle farming that can be used as raw material for producing liquid organic fertilizer. This study aims to determine the effect of the process of obtaining urine waste in cattle farms on the quality of liquid organic fertilizer. The measured parameters include N, P, K, pH, organic-C, and bacterial contamination, in accordance with the Indonesian Ministry of Agriculture Regulation No. 261 of 2019. The method used in this research is fermentation with EM4 decomposer for 30 days. The results of the one-way ANOVA test showed significant differences in pH, organic-C, N, P, and K between B1 and B2, with higher values of pH, organic-C, N, and P in liquid organic fertilizer made from cattle urine mixed with manure. Meanwhile, the K value was higher in liquid organic fertilizer made from pure urine without manure.